Experimental Study on the Tensile Properties of Rock-Mortar Interface under Different Strain Rates - Nan Wu; Zhende Zhu; Zhilei He (Advances in Materials Science and Engineering)
In this paper, an experimental study was carried out on a rock-mortar interface specimen under three different strain rates (10−6, 10−5, and 10−4  s−1) using the MTS322 electrohydraulic servo loading system, and a new constitutive relation function of fictitious crack model (FCM) according to the axial-stress-crack-width curves of the rock-mortar interface is established, because the traditional nonlinear softening function easily distorts, shakes, and so cannot describe the damage-evolution process of the rock-mortar interface accurately. Through the use of a precise servo actuator system and three extensometers measured axial-stress-crack-width curves, it is shown that the rock-mortar interface is very sensitive to the strain rate. The tensile strength increases with strain rate, the crack width decreases at the same time, and the axial-stress-crack-width curves gradually evolve from a concave-downward trend to a linear decreasing trend. At the same time, the new constitutive relation function can reflect the tensile strength, crack width, and the downward trend of the rock-mortar interface more accurately.